[re] Build. [re] Fabrication of District Six: Weaving Heritage Narratives with Future Development - Michaels, Leah (School of Architecture, Planning and Geomatics, 2024)
The history and design process of Architecture has always been an interest of mine due to my family's rich heritage in District Six. All my life I have been told stories of what seemed like a magical, utopian dream space. A place that seemed too good to be true, where neighbors were family and loyalty was stronger than money. A Utopia where the sense of Ubuntu, “I am because we are”, was a reality. A quality that the Democratic South Africa still strives towards. It was because of these stories that my curiosity grew. I wanted to know what made this place so special. It was my grandparents who shared the joyful memories and sparked my interest. One day they said, “if only someone like us was on the panel making decisions, maybe things would've been different.” This is when I knew I wanted a seat at the table where Cape Town's design decisions are made. I believe that Architecture is a tool for outreach and change that can disrupt the cycle of injustice and inequality. I have always felt a responsibility to contribute to the built environment my family once watched being torn down. These stories inspired me and molded me into the designer I aspire to be, hence have become the point of entry into revealing the truths of everyday life within District Six and seeing its cultural significance. My family kept photographs of District Six which acted as the stage which these stories were acted upon. These photos inspired me to dive deeper into images and sources. As a point of entry, a photo of the Avalon Bioscope was not just that, it was the story of my great grandmother attending her weekly movie. A photo of Russel Street showed home.